Simulation of AlGaN MSM detector for investigating the effect varying absorber layer thickness - et. al., Harpreet Kaur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For detecting feeble Ultra-Violet (UV) signals it is essential that front-illuminated photodetector (PD) should havethick photo-absorbing layer with thin transparent metal electrodes and antireflective coating (ARC) so as to getmore photocurrent and low dark current.Since detector geometry influences its performance, so it is very important to optimize layer thickness parameters. In proposed work fixed area Al0.5Ga0.5N/AlN/ Sapphire based Metal-Semiconductor-Metal (MSM)PDbased has been analyzed for optimum value of active layer thickness and inter-electrode thickness.In addition to take benefit of large Schottky barrierGold material has beenutilized for electrodes. It has been illustrated in past research studies that with the increase in thickness of AlGaN layer, more incident energy can be absorbed for large EHPs generation which lead to increased responsivity.However, few research papers have related the effect of variations inthickness of active layerwith electron velocity which has significant effect on dark current density, recombination rateand additionally on efficiency.So for further development and widespread implementation of AlGaN/GaN based detectors there is need to study the effect of variation in photo-absorber layer thickness on closely related performance parameters so as to select its optimum value.Current Voltage (IV)-characteristics,recombination rate, current density plots and spectral response have been investigated using Atlas-Silvaco simulation tool.In addition for electrode thickness variation,transmission and absorptionplots are alsoinvestigated. For the proposed MSM structure, it has been observed that dark current density tends to increase beyond the optimum value of thickness of AlGaN layerwith specific absorption coefficient. Good transmission of light with high spectral response can be obtained with optimum value of electrode thickness.These observations can be suitable for improving the detectivity in support of various UV detection applications requiring good sensitivity and high signal to noise ratio.